POSSIBILITIES OF ORGAN-PRESERVING TREATMENT OF PATIENTS WITH MULTIPNEOADJUVANT COMBINATION CHEMOTHERAPY IN A PATIENT WITH CERVICAL CANCER IIIB STAGE WITH THE USE OF INTRA-ARTERIAL ADMINISTRATION OF PLATINUM DRUGS - A. G. Rerberg; A. A. Kostin; A. V. Boyko; E. G. Novikova; N. N. Volchenko; O. V. Chulkova; L. V. Demidova; G. I. Khokchrikov; D. Yu. Sidorov; A. R. Gevorkyan (Исследования и практика в медицине, 2017)
The main treatment for cervical cancer are surgery, radiation and combined (surgery + radiotherapy), the role of chemotherapy in this localization is studied less fully. In recent years the new possibilities of chemotherapy, including neoadjuvant intraarterial chemotherapy, are explored. Theoretical prerequisites for this are the best drug delivery to the tumor by blood vessels, undamaged due to radiation therapy and surgery. This paper describes a clinical case of a patient with primary inoperable cervical cancer. As an alternative to preoperativ e radiotherapy the patient was proposed neoadjuv ant com bination chemotherapy with the use of regional administration of platinum drugs and systemic administration of drugs of taxan series as a stage of preparation for further surgical treatment. According to the prevalence of the tumor process patient underwent 2 courses of neoadjuv ant chemotherapy by a method of superselective intra-arterial administration of cisplatin and paclitaxel intravenously. According to a comprehensive examination after treatment data for the presence of tumor was absent. During the second stage the patient underwent surgical treatment in the volume of nerve-sparing radical hysterectomy with appendages. The next step, according to the histological form of the tumor, stage of disease, was the radiotherapy in the postoperative period on the pelv ic area and routes of lym ph drainage. The patient underwent external beam radiotherapy to the pelvic area of FD = 20 Gr, intracavitary gamma-therapy and external beam radiation on the area of parametrial and lymphopenia FD = 50 Gr.The patient passed the control examinations every 3 months. According to a comprehensive survey a year after the start of treatment — there is no data for the presence of recurrence and spread of tumor process.